Are Malawian diets changing? An assessment of nutrient consumption and dietary patterns using household-level evidence from 2010/11 and 2016/17 - Gilbert, Rachel; Benson, Todd; Ecker, Olivier (International Food Policy Research Institute, 2019)
NOTE: PDF corrected July 2020 This paper provides an updated analysis of the dietary patterns of Malawian households and their consumption of select nutrients - calories, protein, iron, vitamin A, zinc, and folate - using data from the third (2010/11) and fourth (2016/17) rounds of the Malawi Integrated Household Survey (IHS). Changes in food and nutrient consumption patterns between the two survey periods are examined across household wealth categories and across regions. Dietary diversity and patterns of food and nutrient consumption are found to differ significantly between rural and urban areas. Whereas urban households largely saw slightly increased or stable nutrient consumption between 2010/11 and 2016/17, most households in rural areas saw declines over this period. We also document small shifts in the relative amounts of foods consumed over this six-year period in both rural and urban households, with increased consumption of fish and pulses, legumes, and nuts, and decreases in meat, fruit, dairy, and root and tuber consumption. The contribution of animal-source foods as a share of total protein consumption remains low at between 10 and 20 percent, depending on the region, with the overall share of protein from animal-source foods falling slightly between the two surveys. With regards to adequacy of household diets for meeting nutrient requirements, in the absence of nutrient supplementation, many individuals will be subject to iron, vitamin A, and folate inadequacies. Of particular concern, the poorest households have very low nutrient consumption per person and have diets that rely on only a few foods from a small number of food groups. For all six nutrients, nationally just over half of the total amount of nutrient consumed came from food that was purchased. While we would expect this for urban households, even for rural households more than half of all calories and protein consumed came from foods that were purchased. For micronutrients consumed by rural households, between 40 and 50 percent came from purchased foods. While in the past, own production of food may have provided most Malawian households with most of the nutrients they consumed, this is no longer the case. For most Malawian households, including in rural communities, their food security and dietary nutritional needs now are equally tied to the market as to their own farming, if not more so. Drawing lessons from the analysis here for improving the food consumption data collected in the IHS surveys, more detailed and further disaggregated data would be beneficial, particularly to help estimate nutrients derived from fortified and processed foods. Additional information on how food is shared within households would also allow for a better understanding of nutrient inadequacies at the individual level. Collecting more information on the content of the meals that household members eat away from home would also be helpful in removing some uncertainty in the nutrient consumption estimates made from the data. Finally, additional information on food gifts received could clarify aspects of household coping strategies, the performance of formal social safety nets, and food choice.